ANALISIS DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR CAMAT TEMPULING KABUPATEN INDRAGIRI HILIR - M RAMLI (Indragiri Research Center (ingreat), 2023)
Every organization has provisions that must be obeyed by its members, standards that must be met in order to improve performance. This study aims to determine whether work discipline affects the performance of Tempuling District Office employees in Sungai Salak. In this study the type of data used consisted of qualitative and quantitative data. Data collection techniques were carried out through interviews and submission of questionnaires, as well as library research. From the results of the study it was concluded that there is an influence between work discipline on employee performance appraisal, where the level of work discipline of Tempuling District Office employees in carrying out their duties is still low so that it affects employee performance to be less than optimal. The existence of a fairly strong influence between work discipline on employee performance can be seen from the statistical analysis which is based on the results of the regression analysis where Y = 0.074 + 0.981 X and the adjusted R2 value is 0.974, which means that 97.4% is not optimal employee performance is influenced by work discipline factors low level employees.